Simbolisme Identitas: Makna Budaya di Monumen Tobong dan Hotel Balairung - Hafidhuddin, Muhammad; Lukito, Yulia Nurliani (Universitas Muhammadiyah Palembang, 2024)
The romantic perception of vernacular architecture, often rooted in nostalgia, significantly influences its use as a symbol of cultural identity. Referring to the works of Paul Oliver and Robert Redfield on vernacular architecture, exploring romanticism and attitudes towards vernacular buildings as well as the differences between them. Tobong, a tower structure for brick burning, and Hotel Balairung in Jakarta are examples of two buildings related to vernacular architecture that can symbolize culture and society and the romance of the past. Rooted in local production traditions, Tobong transcends its functional purpose to become a symbol of cultural heritage and the significance of vernacular architecture to this day. Similarly, Hotel Balairung represents the adaptation of the vernacular architecture and culture of West Sumatra, which can symbolize regional pride and economic development. How vernacular structures like Tobong being made into monuments and Hotel Balairung represent the cultural significance and adaptability of vernacular architecture, my argument is that both vernacular architecture buildings, Tobong being made into a monument in Godean Yogyakarta and West Sumatra architecture being used as a hotel in Jakarta, show variations of the significance and adaptability of vernacular architecture in the present era. Through a comparison method of two buildings that elevate vernacular architecture, this article shows the connection between vernacular buildings and their cultural identity, as well as their ability to be used in various contexts of adaptability, and significance in shaping communitiesKeywords: sentiment, vernacular architecture, monument, culture, identity